2009
DOI: 10.1007/s10826-009-9297-3
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ and Fathers’ Responsive Problem Solving with Early Adolescents: Do Gender, Shyness, and Social Acceptance Make a Difference?

Abstract: We assessed the extent to which youths' (n = 231) shyness and social acceptance in preadolescence were associated with parents' responsive problem solving 1 year later after controlling for initial levels of parents' problem solving. Teachers (n = 176) completed assessments of youths' shyness and social acceptance, and parents (n = 231 married pairs) completed assessments of their responsive problem solving with the child. For shy daughters, higher levels of social acceptance from peers predicted more responsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…We were able to support this claim by replicating it four times in this sample (i.e., parent and child shyness were associated with their own communication competence and social control). Researchers have found this association among children, adolescents, and young adults (e.g., Downloaded by [University of Cambridge] at 07:51 03 January 2015 Brunet & Schmidt, 2007;Eggum et al, 2009;Miller, Brody, & Murry, 2010). The current results extend these findings because we found that shyness is related to social skills in young adults and middle-aged adults, suggesting that this association persists across the life span.…”
Section: Discussionsupporting
confidence: 87%
“…We were able to support this claim by replicating it four times in this sample (i.e., parent and child shyness were associated with their own communication competence and social control). Researchers have found this association among children, adolescents, and young adults (e.g., Downloaded by [University of Cambridge] at 07:51 03 January 2015 Brunet & Schmidt, 2007;Eggum et al, 2009;Miller, Brody, & Murry, 2010). The current results extend these findings because we found that shyness is related to social skills in young adults and middle-aged adults, suggesting that this association persists across the life span.…”
Section: Discussionsupporting
confidence: 87%
“…Six studies (Caster et al, 1999;McClure et al, 2001;Miller et al, 2010;Schwartz et al, 2012;Van Zalk & Kerr, 2011;Wijsbroek et al, 2011) were part of larger studies. Participants were recruited through schools in all except four studies (McClure et al, 2001;Miller et al, 2010;Vazsonyi & Belliston, 2006;Wijsbroek et al, 2011), where participants were drawn from the community. One study included a referred, clinical population (Hudson & Rapee, 2001).…”
Section: Study Samplementioning
confidence: 99%
“…All but one study (Rapee, 2009) involved adolescents of both sexes. Six studies assessed adolescents for symptoms related to social anxiety or shyness (Caster et al, 1999;Fisak & Mann, 2010;Garcia-Lopez et al, 2009;Loukas, 2009;Miller et al, 2010;Van Zalk & Kerr, 2011), four studies assessed symptoms of generalized anxiety (Hale III et al, 2006;Muris, 2002;Wijsbroek et al, 2011;Wilson et al, 2011) and Wijsbroek et al (2011) also looked at symptoms of separation anxiety. The remaining twelve studies used measures that assessed general anxiety symptoms.…”
Section: Adolescents and Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…In these days, present studies of parental monitoring are focusing on the influences of parental monitoring and schooling [2], self-control of children [3], and academic achievement [4]. The former studies show that parental monitoring effects on the teen's problem solving skills [5]. However, there is no study focuses on the relationship of parental monitoring, hands-on learning attitude, problem approach attitude, problem solving confidence, and problem solving style.…”
Section: Introductionmentioning
confidence: 99%